1997
DOI: 10.1007/s002640050155
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the accuracy of clinical examination evaluated by arthroscopy of the knee

Abstract: Summary. The diagnostic accuracy of clinical examination for internal derangement of the knee were evaluated by arthroscopy in 195 patients (200 knees). Radiographs were available and 50 patients had magnetic resonance imaging. The clinical diagnosis was correct in 104 knees (52%), incomplete in 70 (35%) and incorrect in 26 (13%). When there was a single abnormality the diagnosis was correct in 70%, but when more than 3 lesions were discovered the figure was 28%. All individual lesions were diagnosed correctly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 23 publications
4
12
0
1
Order By: Relevance
“…MRI's low sensitivity for chondral lesions has been reported before [17]. Our study form included no formal classification of chondral lesions, so we do not know the true nature of the chondral lesions we have missed.…”
Section: Discussionmentioning
confidence: 99%
“…MRI's low sensitivity for chondral lesions has been reported before [17]. Our study form included no formal classification of chondral lesions, so we do not know the true nature of the chondral lesions we have missed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the value of MRI in the acutely injured knee is much debated. Some studies have found that MRI tends to overestimate the number of lesions, while others maintain that clinical examination of the knee alone is too inaccurate to detect all pathological conditions after an injury (Speer, Spritzer, Goldner, Garrett, 1991; Boden et al., 1992; Le Vot & Solacroup 1993; Kinnunen et al., 1994; Helmuth et al., 1996; Mackenzie, Dixon, Keene, Hollingworth, Lomas, Villar, 1996; Rangger et al., 1996; Twaddle et al., 1996; Williams et al., 1996; Yoon et al., 1997). Also it remains to be proven whether MRI findings have any influence on the prognosis for the patient and whether these findings should be reasonable for an alteration in treatment.…”
mentioning
confidence: 99%
“…Yoon et al [48] reported that the correct diagnosis of knee injuries was made in only 52 % of knees, incomplete diagnosis in 35 % of knees, and incorrect diagnosis in 13 % of knees. Oberlander et al [32] reported similar findings with correct diagnosis being made in 56 % of cases, incomplete diagnosis in 31 %, and incorrect diagnosis in 13 %.…”
Section: Discussionmentioning
confidence: 99%